Engaging Young People in Occupations Served by Vocational Education: Case Study From Healthcare - Billett, Stephen; Le, Anh Hai (International Journal for Research in Vocational Education and Training, 2024)
Purpose: Globally, countries with both developed and developing economies are struggling to secure sufficient participation in vocational education to generate the range and quantum of skills required for their communities and realising national social and economic goals. In an era of high aspiration, vocational education and the occupations it serves are increasingly seen as being a less than desirable outcome by young people and their parents. Hence, there is a need to identify means by which to inform and engage young people in considering vocational education and the occupations it serves. The case study discussed in this paper is contextualised within the Australian state of Queensland, which, like many other countries is struggling to have a workforce sufficient to meet communities' healthcare needs as its population both grows and ages. Methods: The study data were collected from 1) interviews with healthcare-related stakeholders including health industry representatives, teachers or practitioners, and healthcare providers, 2) focus groups with senior secondary students, and 3) surveys with these participant groups. It provides a descriptive analysis of efforts to secure greater participation by young people in allied health roles, and, in particular, young Australian Indigenous people. Findings: The study participants included those from regional and metropolitan centres and from state and independent schools, and in all of which the focus on engagement was central. Findings indicated that engagement was necessary to advise young people about these occupations, the effective preparation for them, and likely retention in the workforce. Conclusion: This study highlights the need for intentional strategies to engage young people, their parents/guardians and with those efforts likely needing to be organised and enacted at the local level. This requires collaboration and engagement from education, industry, and local communities. Essentially, a systemic approach is required, specifying roles for government, employers, educational systems, and teachers and parents who engage directly with young people. In all, engagement, advice and opportunities locally are all emphasised in the study reported here.